Updates in the pathophysiology of COVID-19 infection in male reproductive and sexual health: a literature review - Alzahrani, Meshari A.; Alkhani, Khalid O.; Alassaf, Abdullah M.; Alorainy, Jehad I.; Binsaleh, Saleh; Almannie, Raed (Frontiers in Endocrinology, 2024)
This extensive comprehensive review explores the impact of the Coronavirus disease 2019 pandemic on men's sexual and reproductive health. We conducted a literature review focusing on the possible pathophysiology by which severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) affects men's sexual and reproductive systems. We reviewed most of the studies that reported the impact of SARS-CoV-2 infection on the Testicular, Epididymal, Prostatic, and Penile tissue. Also, we focused on evaluating the SARS-CoV-2 infection on semen parameters and male reproductive hormones. Finally, we reviewed the COVID-19 vaccine's effect on male reproductive and sexual health.Findings revealed the adverse consequences of SARS-CoV-2 at cellular and organ levels on the male genital tract. However, the reported data are still controversial. The initial data regarding COVID-19 vaccination was promising promoted safety for men's reproductive and sexual health.We conclude this paper by offering recommendations to address these adverse consequences and potentially improve sexual and reproductive health among men in the post-COVID-19 pandemic era.